Associação do aleitamento materno prolongado e o estado nutricional na idade escolar: um estudo de coorte prospectiva - Pozza, Débora Fernanda Colombara [UNESP] (Universidade Estadual Paulista (Unesp), 2025)
Há inconsistências na literatura sobre as repercussões do aleitamento materno prolongado (AMP) no estado nutricional infantil em curto e médio prazo, especialmente no Brasil, onde essa prática — após 12 ou 24 meses de idade — é pouco estudada, principalmente quanto à sua influência na idade escolar. Este estudo teve como objetivo analisar a frequência do AMP (>12 e >24 meses) na coorte do estudo CLaB – fase II, realizado em 2023/2024, e sua associação com o estado nutricional de crianças em idade escolar. Trata-se de uma coorte prospectiva com crianças nascidas em 2015/2016 e acompanhadas no primeiro ano de vida (n=585), das quais 391 foram localizadas e, após exclusões, 344 foram incluídas. A coleta de dados domiciliares abrangeu informações socioeconômicas, maternas, paternas e de saúde da criança, com aferição de peso e altura. A variável de exposição foi a duração do aleitamento materno, categorizada como AMP >12 meses e AMP >24 meses, e o estado nutricional foi classificado segundo o z-escore do IMC, conforme critérios da OMS. Inicialmente, a associação entre AMP e estado nutricional foi analisada por frequência e teste do qui-quadrado, sendo posteriormente empregada regressão de Poisson com variância robusta, considerando p<0,05 como estatisticamente significativo. A frequência de AMP >12 meses foi de 41% e de AMP >24 meses foi de 12,8%; entre essas crianças, a prevalência de excesso de peso foi semelhante (40,5% e 41,9%, respectivamente), assim como a de baixo peso (7,2% e 7%), sem variação significativa associada ao AMP. Entre os fatores analisados, apenas a ausência de internação em UTI neonatal mostrou associação com maior prevalência de AMP, aumentando em 14% e 16% as chances de AMP >12 e >24 meses, respectivamente. Conclui-se que o aleitamento materno prolongado, seja após 12 ou 24 meses, não influenciou o estado nutricional das crianças aos sete/oito anos, e que a ausência de internação neonatal foi o único fator associado à maior prevalência de AMP, com efeitos pequenos, porém estatisticamente significativos. Assim, considerando os benefícios já consolidados do aleitamento materno para a saúde e desenvolvimento infantil, justificam-se ações para promover sua prática prolongada na localidade, sem risco de prejuízos ao estado nutricional infantil.

There are inconsistencies in the literature regarding the short- and medium-term impacts of prolonged breastfeeding on children's nutritional status, and in Brazil, this practice—whether beyond 12 or 24 months of age—remains underexplored, particularly in relation to school-aged children's nutritional outcomes. This study aimed to analyze the prevalence of prolonged breastfeeding (PBF) beyond 12 and 24 months in the cohort from the CLaB Study – Phase II, and its association with children's nutritional status at school age. It was a prospective cohort study conducted in 2023/24 as part of the second phase of the “Cohort Study of Infants from Botucatu” (CLaB), involving children born in 2015/2016 who had been previously followed during their first year of life (n=585). Of these, 391 were located, and after consistency checks and applying exclusion criteria, the final sample included 344 children. Data collection occurred in participants’ homes, covering updated socioeconomic, maternal, paternal, and child health data, along with measurements of weight and height. The exposure variable was breastfeeding duration, categorized as PBF >12 months and PBF >24 months. Nutritional status (underweight, normal weight, overweight, or obesity) was assessed using BMI z-scores based on WHO criteria. The influence of prolonged breastfeeding on nutritional status was first evaluated by comparing the distribution of children across nutritional categories using the chi-square test, followed by Poisson regression with robust variance, considering associations significant at p<0.05. The prevalence of breastfeeding beyond one year was 41%, and 12.8% of the children were breastfed beyond two years. Among those breastfed for more than 12 and 24 months, the prevalence of excess weight was similar (40.5% and 41.9%, respectively), as was underweight (7.2% and 7.0%), indicating no variation in nutritional status at age seven/eight according to prolonged breastfeeding exposure. Among the potential influencing factors analyzed, only the absence of neonatal intensive care unit (NICU) admission was significantly associated with higher PBF prevalence, increasing the likelihood of breastfeeding beyond 12 and 24 months by 14% and 16%, respectively. In conclusion, prolonged breastfeeding, whether beyond 12 or 24 months, did not impact the nutritional status of children at seven/eight years of age, and while the absence of NICU admission was linked to slightly higher breastfeeding prevalence, the effect was small but statistically significant. Given the established health and developmental benefits of breastfeeding, promoting prolonged breastfeeding in the region is warranted, with no concern for negative effects on children's nutritional status.
Association of extended breastfeeding and nutritional status at school age: a prospective cohort study
Keywords: Aleitamento materno; Saúde materno-Infantil; Ciências da nutrição infantil; Nutrição da criança; Breastfeeding; Maternal and child health; Pediatric nutrition science